Self-perceived oral health among Karnataka state road transport corporation bus drivers and employees in Davanagere city: a cross-sectional survey - Yavagal, Puja C.; Purad, Kishan Shanmukhappa; Raja, Davia; Manjunath, Chaya Basavpura; Mahendra, Disha; Fathima; Naik, Gagana Maheshwara; Shariff, Hajira (International Journal Of Community Medicine And Public Health, 2025)
Background: The health of road public transportation workers is a country’s health concern. Very few studies have been done to address this issue hence a study was planned to assess the self- perceived oral health among Karnataka State Road Transport Corporation (KSRTC) bus drivers and employees in Davanagere city. Methods: A cross-sectional questionnaire study was conducted involving 300 employees (KSRTC Bus drivers, conductors and mechanical workers) of Davanagere city between June to August 2024. Data was collected using WHO Basic Oral health survey self-perceived oral health questionnaire for adults. IBM SPSS Statistics version 19 was used for statistical analysis. Responses of participants were expressed in percentages. Results: Majority of study population were males (96.7%) with an average age of 42.18±6.64 years. The majority (44%) worked as both drivers and conductors. Majority (55%) perceived their oral heath as average, followed by good oral health (27%) and poor oral health (13%). The majority (64%) never received dental care in the past year and 15 % of them visited a dentist due to pain associated with teeth/gums. Around 3% smoked beedi/cigarette occasionally and 1% daily. Around 22% occasionally consumed smokeless tobacco and 12% daily. Around 1-5% had trouble in speech, dry mouth, stained teeth, avoided smiling, had sleep interruption, had remained absent at work, had trouble in doing daily activities, reduced social activity because of oral problems. Conclusions: Majority of Karnataka Road Transport Corporation Bus drivers and employees in Davanagere city reported of having average oral health and few reported of having poor oral health.